Manajemen Strategi Kepala Madrasah dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam (PAI) pada Madrasah Tsanawiyah Negeri 1 Padangsidimpuan - Ummi Kalsum; Erawadi Erawadi; Zulhammi Zulhammi (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to find out how the management strategy of the madrasa head in improving the performance of Islamic religious education (PAI) teachers at Madrasah Tsanawiyah Negeri 1 Padang Sidimpuan. This research uses a qualitative approach with descriptive methods. Research data obtained from interviews with research informants as many as 8 people. There are two data collection techniques in this study, namely observation and interviews. The results showed that the management strategy of the head of Madrasah Tsanawiyah (MTs) Negeri 1 Padangsidimpuan on improving the performance of Islamic Religious Education teachers through socialization and training. The implementation of the Madrasah head's strategic management in improving the performance of Islamic Religious Education (PAI) teachers at Madrasah Tsanawiyah (MTs) Negeri 1 Padang Sidempuan has been carried out. Teacher discipline development is carried out every monthly meeting. Evaluation of the implementation of the Madrasah Principal's strategic management in improving the performance of Islamic Religious Education (PAI) teachers at Madrasah Tsanawiyah (MTs) Negeri 1 Padang Sidempuan can be seen from the performance of Islamic Religious Education (PAI) teachers at Madrasah Tsanawiyah (MTs) Negeri 1 Padang Sidempuan having good performance with a frequency of 96.25% the indicator can be fulfilled. In this case around 3.75% which is not fulfilled is in the shortage of learning media.